The Role of Angiotensin Converting Enzyme 1 Insertion/Deletion Genetic Polymorphism in the Risk and Severity of COVID-19 Infection - Saad, Halim; Jabotian, Karna; Sakr, Carine; Mahfouz, Rami; Akl, Imad Bou; Zgheib, Nathalie K. (Frontiers in Medicine, 2021)
Background Individuals infected with the COVID-19 virus present with different symptoms of varying severity. In addition, not all individuals are infected despite exposure. Risk factors such as age, sex and comorbidities play a major role in this variability; however, genetics may also be important in driving the differences in the incidence and prognosis of the disease. An Insertion/Deletion (I/D) polymorphism in the ACE1 gene (rs1799752) may explain these genetic differences. The aims of this study were to determine the potential role of ACE1 I/D genetic polymorphism in the risk of contracting COVID-19 as well as predicting the severity of COVID-19 infection. Methods Three-hundred and eighty-seven non-related Lebanese subjects, 155 controls and 232 cases, who presented to the American University of Beirut Medical Center (AUBMC) for COVID-19 PCR testing were recruited. Clinical data were collected via filling a questionnaire and accessing the medical records. Peripheral blood was withdrawn for DNA isolation, and genotyping performed with standard PCR followed by band visualization on agarose gel. Results In our study population, previously described risk factors such as gender, age, and comorbidities were associated with increase in disease susceptibility and severity. ACE1 I was the least common allele, and there was a positive association between ACE1 I and the risk of contracting the COVID-19 disease. More specifically, the frequency of II genotype was significantly higher among cases when compared to controls (P=0.035) with individuals with the II genotype having greater risk for contracting the COVID-19 disease: OR=2.074, P=0.048 in the multivariate analysis. As for disease severity, the DD genotype and D allele were associated with increased risk for developing severe symptoms (OR=2.845, P=0.026 and OR=2.359, P=0.014 respectively), and the DD genotype with necessitating hospitalization (OR=2.307, P=0.042,). In parallel, D allele carriers showed a significantly increased risk for developing hypoxia: OR=4.374, P=0.045. Conclusion We found a positive association between ACE1 I and the risk of contracting the COVID-19 disease, and between ACE1 D and a worse outcome of the COVID-19 infection. Therefore, genotyping for ACE1 I/D polymorphism could be used to assess risk and predict severity for better prognosis and management of the disease.